Ikhwan Chocolate / Sarah Hazraty Azman - Azman, Sarah Hazraty (2020)
GISB HOLDINGS is an Islamic Bumiputera company. The Company was founded by Ustaz Ashaari Muhammad with the aim to develop the islamic way of life in all aspects of life such as education, arts and culture, animal farming,etc . The company’s HQ is at Rawang , Selangor. The company has many branches even outside of Malaysia for example at Turkey, UK, Germany, Egypt, etc. The company is very successful and has many stores, shops and even restaurants. They also have their own products such as roti ikhwan , sos ikhwan , tepung gandum ikhwan , and so much more including the product i’m using which is ikhwan chocolate.Ikhwan chocolate is one of their products and is 100% halal. They have various flavors and sizes including in jars.